GE_GERICHTE C/26005/2012 vom 26. August 2016 - GE Cour de justice (2016)
CONTRAT D'ENTREPRISE ; MANDAT ; RÉSOLUTION DU CONTRAT ; REDDITION DE COMPTES ; CONTRAT SUI GENERIS | CO.363; CO.394; CO.400; CO.404;